If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + -1k = p + -14 Reorder the terms: 2j + -1k = -14 + p Solving 2j + -1k = -14 + p Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add 'k' to each side of the equation. 2j + -1k + k = -14 + k + p Combine like terms: -1k + k = 0 2j + 0 = -14 + k + p 2j = -14 + k + p Divide each side by '2'. j = -7 + 0.5k + 0.5p Simplifying j = -7 + 0.5k + 0.5p
| 2w+5+3=58 | | f(3)=2.5 | | f(2.5)=3 | | -6x+5(5x+4)=134 | | 5.8x+5=4.8x | | 40=7x-9 | | z+12.1=-5.9 | | (4x-20)=61 | | 9x+5x+4+9=5x+4+8x | | -4x-3(-4x-15)=117 | | 9n-6=12 | | 15p-19p=8 | | 24+197y=24+197*5 | | s+25=18 | | X+y=o | | 12h-5h=48 | | 36-6n=-6(1+2n) | | 5j+7j=144 | | 4+5*4=2f | | 6m+8+5m-5=85 | | 8x+2=2x-4 | | 3.6q-2.2-4.3q=-1.7q-4.4 | | -3=x-2x | | 2.7q-2.5-5.7q=-4.0q-3.9 | | 2(3x+2)=7x-4 | | x-5x=16 | | 3(2x+5)=27 | | x^2-10x-72=0 | | 4-(2x-1)=19 | | x^2-8x+16=54 | | 6x-6=2x-18 | | 10=-3k-2k |